How Effective Is Iron Supplementation During Pregnancy and Childhood in Reducing Anemia Among 6–59 Months Old Children in India? - Thomas, Monica Steffi; Demirchyan, Anahit; Khachadourian, Vahe (Frontiers in Public Health, 2020)
Objectives: The study sought to identify whether iron and folic acid supplementation of pregnant women and preschool children are associated with child’s anemia status and the predictors of anemia among children in India. Design: Secondary data analysis was performed using the National Family Health Survey 4 data. Multivariable logistic regression was used to identify the adjusted associations between child’s anemia status and iron supplementation, both during pregnancy and childhood. Also, a model of significant predictors of anemia among children was fitted. Setting: India. Participants: Youngest children in families aged 6 – 59 months. Results: The adjusted association between supplementation during pregnancy and child’s anemia status was significant (p=0.010), whereas the adjusted association between supplementation during childhood and child’s anemia status was insignificant (p=0.16). The variables independently associated with anemia status of the child included younger age (95% CI 2.67-2.86), child’s recent diarrhea (95% CI 1.02-1.14), low birth weight (95% CI 1.17-1.27), current underweight (95% CI 1.14-1.28), diet diversity score (95% CI 0.96-0.98), higher birth order (95% CI 1.01-1.05), mother’s current anemia (95% CI 1.68-1.81), months of breastfeeding (95% CI 0.99-1.00), no/primary education (95% CI 1.23-1.35), family’s low wealth index (95% CI 1.11-1.23) and backward caste (95% CI 1.04-1.14). Conclusions: The National Iron Plus Initiative strategy of child’s iron supplementation should be evaluated to identify the reasons of its ineffectiveness in anemia reduction. In addition, vulnerable groups of children, i.e. children from poor and less educated families, those with low birth weight, higher birth order, and poor nutritional status should be targeted first with anemia reduction interventions.